Work experience and graduate migration: an event history analysis of German data. Issue 10 (2nd October 2020) - Teichert, Christian; Niebuhr, Annekatrin; Otto, Anne; Rossen, Anja
ABSTRACT: Administrative social security records and event history analysis are used to investigate the significance of previous work experience for the migration decision of German university graduates. The regression results suggest that work experience gained previously and while studying in the university region reduces the likelihood of graduates out-migrating, while extra-regional work activity enhances the probability of labour market entry outside the region of study. The size of the effect depends on the type of work experience. The findings point to the importance of knowledge about local labour markets and social networks for graduates' migration decision at the start of their career.